2015
DOI: 10.1080/10691898.2015.11889748
|View full text |Cite
|
Sign up to set email alerts
|

The Statistical Content of Elementary School Mathematics Textbooks

Abstract: , all rights reserved. This text may be freely shared among individuals, but it may not be republished in any medium without express written consent from the authors and advance notification of the editor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 12 publications
1
19
0
2
Order By: Relevance
“…This diverges from other studies of the statistics content of mathematics textbooks (i.e. Bargagliotti, 2012;Jones et al, 2015;Jones & Jacobbe, 2014;Pickle, 2012;Tran, 2013), which have predominantly focused on the types of actions that the tasks involve related to the statistical investigative cycle outlined in the GAISE framework (Franklin et al, 2007). Another difference is that drawing from Foucault's notion of discourse and his methodology brings with it an epistemological position that acknowledges the power of discourses in texts, to shape what knowledge is, and the reality we are subjected to.…”
Section: Discoursementioning
confidence: 77%
See 1 more Smart Citation
“…This diverges from other studies of the statistics content of mathematics textbooks (i.e. Bargagliotti, 2012;Jones et al, 2015;Jones & Jacobbe, 2014;Pickle, 2012;Tran, 2013), which have predominantly focused on the types of actions that the tasks involve related to the statistical investigative cycle outlined in the GAISE framework (Franklin et al, 2007). Another difference is that drawing from Foucault's notion of discourse and his methodology brings with it an epistemological position that acknowledges the power of discourses in texts, to shape what knowledge is, and the reality we are subjected to.…”
Section: Discoursementioning
confidence: 77%
“…Though textbooks do not dictate the enacted curriculum of the mathematics classroom, in the case of statistics, where teachers often do not have much prior experience with the subject (Shaughnessy, 2007), textbooks may be highly influential in shaping the enacted curriculum of the classroom. However, up to this point there has been very little investigation of the statistics content of school mathematics texts in the U.S. (Bargagliotti, 2012;Jones et al, 2015;Jones & Jacobbe, 2014;Pickle, 2012;Tran, 2013). This dearth of research is concerning given that statistics and mathematics are distinct disciplines, meaning there are differences in how it should be taught as well.…”
Section: Objectivesmentioning
confidence: 99%
“…There also needs to be large scale professional development provided for those teachers already in the classroom. Another issue is that as past research on the statistics content of mathematics texts in the K-12 setting have shown, statistics content is often put in a single standalone unit, and generally makes up only a small portion of the overall text in comparison to other content areas such as number and quantity (Jones et al, 2015;Jones & Tarr, 2010). It is important that statistics content is integrated more into the mathematics curriculum so it is not easily skipped or ignored, but becomes an integral component of the mathematics curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…En Educación Primaria, diversos estudios han analizado la presencia de estadística y la probabilidad en los libros de texto (ABED; AL-ABSI, 2015; DÍAZ-LEVICOY; VÁSQUEZ; MOLINA-PORTILLO, 2018; GÓMEZ-TORRES; ORTIZ; GEA, 2014;JONES et al, 2015;SALCEDO, 2015;ALSINA, 2015ALSINA, , 2017; entre otros). Jones et al (2015), por ejemplo, han analizado cinco colecciones de Estados Unidos para alumnos de los grados 1-5 (6-12 años aproximadamente) y concluyen que dos colecciones ubican la mayoría del contenido estadístico cerca del final del texto, mientras que otras dos colecciones ubican las tareas estadísticas de manera más uniforme en todo el libro de texto. En todos los casos, la mayoría de las tareas estadísticas requieren que los estudiantes analicen datos, con un fuerte énfasis en las actividades de lectura de pantallas y realización de cálculos matemáticos, lo cual pone en evidencia un desajuste considerable con las directrices curriculares americanas.…”
Section: Marco Teóricounclassified